Strong spatial structure, Pliocene diversification and cryptic diversity in the Neotropical dry forest spider Sicarius cariri - Fiorini de Magalhaes, Ivan Luiz (2014)
The Brazilian Caatinga is part of the seasonally dry tropical forests, a vegetation type disjunctly distributed throughout the Neotropics. It has been suggested that during Pleistocene glacial periods, these dry forests had a continuous distribution, so that these climatic shifts may have acted as important driving forces of the Caatinga biota diversification. To address how these events affected the distribution of a dry forest species, we chose Sicarius cariri, a spider endemic to the Caatinga, as a model. We studied the phylogeography of one mitochondrial and one nuclear gene and reconstructed the paleodistribution of the species using modelling algorithms. We found two allopatric and deeply divergent clades within S. cariri, suggesting that this species as currently recognized might consist of more than one independently evolving lineage. Sicarius cariri populations are highly structured, with low haplotype sharing among localities, high fixation index and isolation by distance. Models of paleodistribution, Bayesian reconstructions and coalescent simulations suggest that this species experienced a reduction in its population size during glacial periods, rather than the expansion expected by previous hypotheses on the paleodistribution of dry forest taxa. In addition to that, major splits of intraspecific lineages of S. cariri took place in the Pliocene. Taken together, these results indicate S. cariri has a complex diversification history dating back to the Tertiary, suggesting the history of dry forest taxa may be significantly older than previously thought.